The BELLE Electromagnetic Calorimeter and its Upgrade to BelleII. (20th July 2017) - Cecchi, C.; Aloisio, A.; Baccaro, S.; Branchini, P.; Cemmi, A.; Lucia, E. De; Nardo, G. De; Sangro, R. De; Epifanov, D.; Finocchiaro, G.; Fiore, S.; Giordano, R.; et al.
Abstract: The new SuperKEKB collider will be an upgrade of the existing KEKB electron-positron asymmetric machine, with a target luminosity of 8×10 35 cm −2 s −1, about 40 times greater than the previous one. The accelerator upgrade is based on the novel low-emittance "nanobeams" scheme. The detector will also be upgraded to cope with the higher luminosity, pile-up and occupancy. We report on the development of the new pure CsI calorimeter for the forward region. An intensive R&D has been carried out to study the performance of pure CsI crystals with Large Area Avalanche Photodiodes readout (LAAPD). Results on the signal to noise ratio for different sensors and front end electronics configurations will be presented as well as the use of filters and wavelength shifters. Measurements with a source, simulating the background machine, have been performed and will also be presented.